2014
DOI: 10.1590/s1679-78252014001200007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of different sleeper typologies and track layout on railway vibrations

Abstract: The last years, ground vibrations have become an important study field due to the increase of the transports needs for society and its amount of running trains associated. The vibrations caused by trains are an important comfort and environmentally problem affecting more people every day. This is an experimental paper which compare the vibrational response of the different sleepers disposed on the line. The section presents different sleepers due to a recent actuation to solve instability phenomena . The vibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The use of auxiliary rails reduced the rail variation deflection along the transition zone [13]. Real investigated the influence of the railway component on the vibration behavior of the track and found that the vibration in the concrete sleeper is lower than the one in the wood sleeper [14]. Sol-Sánchez found that the use of deconstructed end-of-life tires in the manufacture of rail pads improves the performance of rail tracks [15].…”
Section: Introductionmentioning
confidence: 99%
“…The use of auxiliary rails reduced the rail variation deflection along the transition zone [13]. Real investigated the influence of the railway component on the vibration behavior of the track and found that the vibration in the concrete sleeper is lower than the one in the wood sleeper [14]. Sol-Sánchez found that the use of deconstructed end-of-life tires in the manufacture of rail pads improves the performance of rail tracks [15].…”
Section: Introductionmentioning
confidence: 99%
“…(15) The EVA system (15) applies infrared beam sensors for stationary train detection, which results in significant expenses. Other detection systems include vibration detection, (16)(17)(18) passive infrared and ultrasonic detection, video imaging, sound detection of locomotive horn, communication-based train detection with onboard Global Positioning System (GPS) and wayside radio links. (15) However, these methods either require expensive equipment and large maintenance load or they are susceptible to interference from various factors such as light condition and environmental temperature.…”
Section: Introductionmentioning
confidence: 99%